FAKTOR-FAKTOR YANGMEMPENGARUID PERMINTAAN KREDIT SEKTOR PERTANIAN DAN KONTRIBUSI SEKTOR PERTANIAN TERHADAP PEREKONOMIAN NASIONAL - Triandy Meinardi; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2007)
This research aims to knowfactors influencing demand of agricultural credit and to know how much agricultural sector contribution to growth of national economics. This research use a time series data of 1980 -2006 obtained from various sources like Badan Pusat Statistik, Bank Indonesia and other related institution and also some related website. Analytical method use table analysis to know the contribution of agricultural sector to growth national economics and linear regression analysis to know thefactors influencing demand of agricultural credit. The result of this research indicates that agricultural sector formerly the biggest contributor of Indonesian economics in 1980-1991, but to lack the second after processing industry in 1991-2001 and become the third biggest after processing industry and trading, restaurant and hotel in 2001-2006. The factors influencing demand of agricultural credit are inflation rate, the rate of interest, economies growth, agricultural labour, agricultural export, import and gold price.